Report on the extensionist experience as an online event: “III Meeting of Microbiology, Immunology and Biotechnology” (Research, Society and Development, 2023)
The pandemic promoted positive vicissitudes in relation to traditional methods of education, popularizing remote teaching. With the aim of continuing to provide knowledge in the health and biological sciences, this experience report will discuss a complementary activity designed in October 2020, aimed at students of dentistry and physiotherapy courses who were having remote teaching. In 2021 and 2022 it was transformed into a sporadic extension action, continuing to be carried out in the online modality, with an expansion of the target audience that also included undergraduates of biology, nursing, medicine and pharmacy courses, with the aim of promoting and propagating a space of education, science and health in times of the Covid-19 pandemic. In this way, through lectures, the events took place in digital format, free of charge and bringing together an expressive and growing number, year after year, of students and professionals with an interest in the areas of Microbiology, Immunology and Biotechnology. The importance of the alternative via the Internet was identified for the democratization of access to education and also for the dissemination of necessary and updated research in the areas disclosed in this meeting.